An efficient one-pot strategy for the synthesis of 4- methylene-2-thiazolidinethiones in water. Issue 10 (18th May 2020) - Hou, Chang-Long; Wei, Mei-Hong; Chen, Li-Li; Liu, Xiao-Ling; Sheng, Shou-Ri
Abstract: A simple and efficient, one-pot strategy for the preparation of 4-methylene-2-thiazolidinethiones has been developed. This protocol involved condensation of primary amines with carbon disulfide in water to generate the dithiocarbamate salts in situ, which coupled with 2, 3-dibromopropene, followed by intramolecular cyclization to the corresponding heterocycles in moderate to good yields. Graphical Abstract: